Assessing the ecological health of rivers when they are dry. (February 2018) - Steward, Alisha L.; Negus, Peter; Marshall, Jonathan C.; Clifford, Sara E.; Dent, Catherine
Highlights: Dry riverbeds are overlooked in river health monitoring and assessment programs. There are no established biological indicators of dry riverbed health. Terrestrial invertebrates responded to a widespread disturbance gradient. Richness and abundance were significantly limited at disturbed sites. We demonstrate how terrestrial invertebrates can be used as health indicators. Abstract: Rivers and streams that dry up are found on every continent, and can form a large proportion of river networks. When rivers are dry, traditional indicators of river health – such as aquatic macroinvertebrates, fish or water quality – cannot be measured. Aquatic health indicators are widely used to assess wetted habitats, but currently no universally applicable indicators have been developed or applied to assess dry riverbed health. Dry riverbeds are often the 'typical' state of many intermittent rivers and streams; however, the ecological health of these habitats is rarely, if ever, assessed in monitoring programs. Resource managers have called for indicators of intermittent river health during the dry phase. The use of terrestrial invertebrate biota (e.g. ants, beetles, and spiders) as indicators in this study provides a novel solution to assessing rivers when they are dry. We developed a conceptual model of human-induced stressors (i.e. disturbance by livestock and feral mammals) on dry riverbed biota, which guided the selection of potential health indicators. Livestock and feral mammals are one of the most significant stressors on riverine ecosystems in Queensland, and impact riverbeds by altering the substrate through compaction, rooting and pugging. We trialled the use of metrics of terrestrial invertebrate assemblages as indicators of dry riverbed health in four Australian dryland catchments: Bulloo, Paroo, Warrego and Nebine. We used quantile regression and found that terrestrial invertebrate communities responded negatively (and significantly, p < 0.05) to a gradient of disturbance, defined by on-the-ground field measurements of livestock and feral mammal impacts. This response to stressors was predicted by the initial conceptual model. We conclude that terrestrial invertebrates in this study are suitable indicators of dry riverbed health, as they are impacted by disturbance from livestock and feral mammals. They can be used in the same way that indicators, such as aquatic macroinvertebrates, are traditionally used to assess river health. We also successfully combined indicators of wet and dry habitats to provide a holistic assessment of the health of intermittent river ecosystems incorporating all sections of the river network. We suggest that this approach should be adopted by other river health monitoring programs in rivers around the world.